Rhizobiales as functional and endosymbiontic members in the lichen symbiosis of Lobaria pulmonaria L. - Erlacher, Armin; Cernava, Tomislav; Cardinale, Massimiliano; Soh, Jung; Sensen, Christoph W.; Grube, Martin; Berg, Gabriele (Frontiers in Microbiology, 2015)
Rhizobiales (Alphaproteobacteria) are well-known beneficial partners in plant-microbe interactions. Less is known about the occurrence and function of Rhizobiales in the lichen symbiosis, although it has previously been shown that Alphaproteobacteria are the dominating group in growing lichen thalli. We have analyzed the taxonomic structure and assigned functions to Rhizobiales within a metagenomic dataset of the lung lichen Lobaria pulmonaria L. One third (32.2%) of the overall bacteria belong to the Rhizobiales, in particular to the families Methylobacteriaceae, Bradyrhizobiaceae and Rhizobiaceae. About 20% of our metagenomic assignments could not be placed in any of the Rhizobiales lineages, which indicates a yet undescribed bacterial diversity. SEED-based functional analysis focused on Rhizobiales and revealed functions supporting the symbiosis, including auxin and vitamin production, nitrogen fixation and stress protection. We also have used a specifically developed probe to localize Rhizobiales by confocal laser scanning microscopy after fluorescence in situ hybridization (FISH-CLSM). Bacteria preferentially colonized fungal surfaces, but there is clear evidence that members of the Rhizobiales are able to intrude at varying depths into the interhyphal gelatinous matrix of the upper lichen cortical layer and that at least occasionally some bacteria also are capable to colonize the interior of the fungal hyphae. Interestingly, the gradual development of an endosymbiotic bacterial life was found for lichen- as well as for plant-associated bacteria. The new tools to study Rhizobiales applied in this study, FISH microscopy and comparative metagenomics will help to better understand the beneficial roles for their hosts and their biotechnological potential.